2017
DOI: 10.22159/ajpcr.2017.v10i5.17347
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Bioactive Compounds From Unknown Marine Sponges Collected From Kovalam, Chennai

Abstract: Objective: This study is designed to hunt for the presence of bioactive compounds from three marine sponges collected from Kovalam.Methods: Zoochemical analysis is performed to screen for the presence of secondary metabolites. Based on those results, only two sponges which showed a significant presence of secondary metabolites has been subjected to gas chromatography-mass spectrometry (GC-MS) analysis to identify the unknown chemical compounds present in those sponges.Results: On analyzing the results, two spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[22]. Cyclohexasiloxane dodecamethyl isolated from marine sponge S. pumila is reported to have many industrial applications and in household care products [23]. 1,2 Napthhalenedione-6-hydroxy has biological activities such as Larvicidal, antibacterial, antifungal, antiviral, insecticidal, anti-inflammatory, and antipyretic activity.…”
Section: Discussionmentioning
confidence: 99%
“…[22]. Cyclohexasiloxane dodecamethyl isolated from marine sponge S. pumila is reported to have many industrial applications and in household care products [23]. 1,2 Napthhalenedione-6-hydroxy has biological activities such as Larvicidal, antibacterial, antifungal, antiviral, insecticidal, anti-inflammatory, and antipyretic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews showed that flavonoids possess wide spectrum of biological activities in cardiovascular system, which include antioxidant, antithrombotic, antiapoptic, anti-ischemic, antiarrhythmic, and anti-hypertensive activities [12,13]. Saponins have considerable commercial value and were processed as drugs and medicines, foaming agents, sweeteners, taste modifiers and cosmetics [14,15]. Furthermore, saponins are neutraceutically important sine its derivative can be easily absorbed by gut secretions and its glycosidic linkage is easily cleaved of [16].…”
Section: Secondary Metabolites Screeningmentioning
confidence: 99%
“…Thành phần các chất sinh học ở hải miên phụ thuộc vào loài, loài Aurora globostellata có alkaloid và fl avanol, không có tannin, nhưng loài Spirastrella inconstans varmoeandrina Dendy có tannin, fl avonol và alkaloid [12]. Thành phần các chất trong dich chiết hải miên phụ thuộc vào dung môi chiết và loài hải miên, cụ thể dịch chiết trong methanol từ loài Dysidea herbacea chứa cả tannin, fl avonoid, alkaloid và phenol, dịch chiết methanol từ loài Sigmadocia pumila có fl avonoid, phenol, alkaloid và thêm cả quinone, nhưng không có tannin, đối với dịch chiết methanol từ loài Acanthella elongate lại chỉ tìm thấy alkaloid, phenol và tannin; đối với dịch chiết dich loromethane từ các loài Dysidea herbacea, Sigmadocia pumila và Acanthella elongate thì phenol chỉ tìm thấy trong dịch chiết dich loromethane từ loài Dysidea herbacea, quinone lại tìm thấy ở dịch chiết dich loromethane từ các loài Sigmadocia pumila và Acanthella elongate [13]. Từ các phân tích ở trên cho thấy sự đa dạng về thành phần các chất sinh học có trong hải miên ở những vùng khác nhau, loài khác nhau.…”
Section: Phương Pháp Xử Lý Số Liệuunclassified